Association between the level of high-sensitivity troponin I (Hs-Trop I) and major adverse cardiovascular events in patients with acute myocardial infarction of segment elevation (STEMI) with primary percutaneous coronary intervention (PCI) - Daniel Daniel; Firandi Saputra; Hendry Purnasidha Bagaswoto; Budi Yuli Setianto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
ST-segment elevation myocardial infarction (STEMI) is a condition which increases the risk of developing major adverse cardiovascular events (MACEs). For patients with STEMI, an efficient method of risk stratification is necessary in order to evaluate the clinical outcome. Troponin has been commonly used in the diagnosis of both STEMI and NSTEMI. The use of high sensitivity assays of troponin has been extensively studied in order to measure the size of myocardial damage caused by STEMI. This study aimed to investigate the association between the level of high sensitivity troponin I (Hs-Trop I) and the incidence of MACEs in patients with primary percutaneous coronary intervention (PCI) in Dr. Sardjito General Hospital, Yogyakarta, Indonesia. It was a cross-sectional observational analytic study involving a total of 195 patients. Data were obtained from both the SCIENCE (Sardjito Cardiovascular Intensive Care) registry and the medical record of Dr. Sardjito General Hospital. Pearson’s Chi square test to evaluate the association between variables was applied. To determine the effect of confounding variables, a multivariate analysis was used. A significant difference in the baseline characteristics between the supramedian and inframedian Hs-Trop I groups (cutoff value of 2063.8 ng/mL) in age, onset, total ischemic time, wire crossing time and the smoking history of both groups was observed. Bivariate analysis showed a significant associations between Hs-Trop I and MACEs (p = 0.033), acute heart failure (p = 0.009) as well as mortality (p = 0.024). Meanwhile, no significant association between Hs-Trop I and cardiogenic shock (p = 0.977) and malignant arrythmia (p = 0.551) was reported. Furthermore, multivariate analysis showed Hs-Trop I, age and wire crossing time were significantly associated with the incidence of MACEs (p = 0.045). In conclusion, there is a significant association between the Hs-Trop I levels and the MACEs events in STEMI patients with primary PCI in Dr. Sardjito General Hospital, Yogyakarta, Indonesia.